Fanon : the postcolonial imagination - Gibson, Nigel C. (Key contemporary thinkers (Cambridge, England), 2003)
Frantz Fanon was a French psychiatrist turned Algerian revolutionary of Martinican origin, and one of the most important and controversial thinkers of the postwar period. A veritable "intellect on fire," Fanon was a radical thinker with original theories on race, revolution, violence, identity and agency.